Strengthening Social Interactions and Constructing New Oral Health and Health Knowledge: The Co-design, Implementation and Evaluation of A Pedagogical Workshop Program with and for Homeless Young People - Andrea Rodriguez; Laura Beaton; Ruth Freeman (MDPI AG, 2019)
Young homeless people make up nearly one-third of those experiencing homelessness. The need to provide an educative approach, to strengthen social interacting, and construct new knowledge to increase social inclusivity, is required. The aim of this qualitative exploration was to use critical consciousness as an educative tool, to co-design, implement, and evaluate a series of oral health and health pedagogical workshops to strengthen social engagement and to construct new health knowledge, with, and for, homeless young people and their service providers. An action research design permitted the simultaneous development, implementation, and evaluation of the pedagogical workshop program. A Non-Governmental Organization (NGO), providing supported accommodation for young homeless people, acted as the partner organization. Thirteen young people and five staff members from this NGO participated and co-designed eight workshops. Qualitative data collection included unstructured post-intervention interviews together with verbatim quotes from the group discussions during the workshops and from the post-workshop questionnaires. The qualitative analysis was informed by content analysis to permit the emergence of key themes from the data. The two themes were: 1. ‘trust building and collective engaging’ and 2. ‘constructing knowledge and developing skills’. Theme 1 highlighted engagement with the service provider, illustrating the transformation of the young people’s relationships, strengthening of their social interacting, and enabling their critical reflexive thinking on sensitive issues present in the homelessness trajectory. Theme 2 illustrated the young people’s ability to share, lend, and encode their new health information and convert it into an understandable and useable form. This new comprehension permitted their behavior change and social interaction. These findings provide an approach to increase young people’s knowledge, health literacy, and strengthen their social interacting to support community action.